Adjuvant chemotherapy in early‐stage endometrioid endometrial cancer with >50% myometrial invasion and negative lymph nodes. Issue 4 (April 2021) - Multinu, Francesco; Garzon, Simone; Weaver, Amy L; McGree, Michaela E.; Sartori, Enrico; Landoni, Fabio; Zola, Paolo; Dinoi, Giorgia; Aletti, Giovanni; Block, Matthew S; Gadducci, Angiolo; Mariani, Andrea
Abstract : Objective : The role of adjuvant chemotherapy as an addition or alternative to radiotherapy for early‐stage high‐risk endometrioid endometrial cancer is controversial. This study aimed to investigate the role of adjuvant chemotherapy in early‐stage high‐risk endometrioid endometrial cancer. Methods : We identified patients with stage I or II endometrioid grade 2 or 3 endometrial cancer with myometrial invasion >50% and negative lymph nodes after pelvic with or without para‐aortic lymphadenectomy at four institutions (USA and Italy). Associations between chemotherapy and cause‐specific and recurrence‐free survival were assessed with Cox proportional hazards models. Hematogenous, peritoneal, and lymphatic recurrences were defined as 'non‐vaginal'. Results : We identified 329 patients of mean (SD) age 66.4 (9.8) years. The median follow‐up among those alive was 84 (IQR 44‐133) months. The 5‐year cause‐specific survival was 86.1% (95% CI 82.0% to 90.4%) and the 5‐year recurrence‐free survival was 82.2% (95% CI 77.9% to 86.8%). Stage II (vs stage IB) was associated with poorer cause‐specific and recurrence‐free survival. A total of 58 (90.6%) of 64 patients who had chemotherapy had 4‐6 cycles of platinum‐based regimen. In adjusted analysis, we did not observe a statistically significant improvement in cause‐specific survival (HR 0.34; 95% CI 0.11 to 1.03; p=0.06) or non‐vaginal recurrence‐free survival (HR 0.36; 95% CI 0.12 to 1.08; p=0.07) with adjuvant chemotherapy. Sixteen of 18 lymphatic recurrences (88.9%; 3/5 pelvic, all 13 para‐aortic) were observed in the 265 patients who did not receive adjuvant chemotherapy. Among stage II patients, no deaths (100% 5‐year recurrence‐free survival) were observed in the eight patients who received adjuvant chemotherapy compared with 66% 5‐year recurrence‐free survival in the 34 patients who did not. Conclusion : Although we observed that adjuvant chemotherapy was associated with improved oncologic outcomes in early‐stage high‐risk endometrioid endometrial cancer, the associations did not meet conventional levels of statistical significance. Further research is warranted in this relatively uncommon subgroup of patients.